Safety and Efficacy of Personalized Cancer Vaccines in Combination With Immune Checkpoint Inhibitors in Cancer Treatment - Liao, Juan-Yan; Zhang, Shuang (Frontiers in Oncology, 2021)
Cancer immunotherapy can induce sustained responses in patients with cancers in a broad range of tissues, however, these treatments require theoptimized combinedtherapeutic strategies.Despite immune checkpoint inhibitors(ICIs)have lasting clinical benefit, researchers are trying to combine them with other treatment modalities, and among them the combination with personalized cancer vaccines isattractive. Neoantigens, arising from mutationsin cancer cells,can elicit strong immune response without central tolerance and out-target effects, which is a truly personalized method. Growing studies show that the combination can elevate the antitumor efficacy with acceptable safety and minimal additional toxicity compared with single agent vaccine or ICI.Herein,we have searched these preclinical and clinical trials andsummarized safety and efficacy of personalized cancer vaccines combined with ICIs in several malignancies.Meanwhile, we discuss the rationale of the combination andfuturechallenges.